Gender Differences and Stereotypes in Teacher Resilience Research - Silvia Barnová; Marek Vochozka; Slávka Krásna; Gabriela Gabrhelová; Denis Barna (Emerging Science Journal, 2024)
In the present study, the issues of teacher resilience and the persistent gender stereotypes in the field are discussed. The main objective of the conducted research study was to examine the presence of gender-stereotype-confirming behavior in coping with adversity in vocational school teachers. The Connor-Davidson Resilience Scale CDRISC-25SLOVAKwas selected as the most suitable research instrument, by means of which gender differences in the participants' (N=474) responses in its subscales were studied. The results obtained confirmed the hypothesis presuming the existence of gender differences in the achieved scores in five of the seven dimensions of the scale, and also stereotype-confirming behaviors”according to which men are rational problem solvers while women tend to apply emotion-focused coping strategies”were reported. This knowledge can be the first step towards introducing measures with the aim to provide individuals of all genders with opportunities to broaden their scale of coping strategies and promote resilience in them. Since vocational school teachers are on the periphery of researchers' interest and no available extensive study has been focused on gender differences in teacher resilience, the research findings aim to fill the gap in the existing knowledge, provide unique data for policymakers, and create a basis for further resilience research. Doi: 10.28991/ESJ-2024-SIED1-011 Full Text: PDF